The Influence of Current Ratio, Inventory Turnover Ratio, Cash Turnover and Debt To Equity Ratio Against The Return on Investment in The Production of Industrial Companies Listed on The Stock Exchange of Malaysia in 2016 - Umniati, Rika; Titisari, Kartika Hendra; Chomsatu, Yuli (Benefit: Jurnal Manajemen dan Bisnis, 2018)
Abstract : This research aims to know the influence of Current Ratio, Inventory Turnover Ratio, Cash Turnover and Debt To Equity Ratio against the Return On Investment. The population in the study, namely the production of industrial companies listed on the stock exchange of Malaysia Year 2016 totalling 233 companies. Type of this research is quantitative research. Sampling using a purposive sampling technique. The number of samples as many as 131 research company. Methods of data analysis used in the study are using multiple linear regression test. Data analysis using SPSS 17 assistance. The results of this study indicate that a variable Inventory Turnover Ratio effect on Return On Investment. While the Current Ratio, variable Cash Turnover and Debt To Equity Ratio has no effect against a Return On InvestmentAbstraksi :Â Penelitian ini bertujuan untuk mengetahui pengaruh Current Ratio, Rasio Perputaran Persediaan, Perputaran Kas dan Rasio Hutang terhadap Ekuitas terhadap Return On Investment. Populasi dalam penelitian, yaitu produksi perusahaan industri yang terdaftar di bursa efek Malaysia Tahun 2016 berjumlah 233 perusahaan. Jenis penelitian ini adalah penelitian kuantitatif. Pengambilan sampel menggunakan teknik purposive sampling. Jumlah sampel sebanyak 131 perusahaan penelitian. Metode analisis data yang digunakan dalam penelitian ini menggunakan uji regresi linier berganda. Analisis data menggunakan bantuan SPSS 17. Hasil penelitian ini menunjukkan bahwa variabel Inventory Turnover Ratio berpengaruh terhadap Return On Investment. Sedangkan Current Ratio, variabel Cash Turnover dan Debt To Equity Ratio tidak berpengaruh terhadap Return On Investment.